Esterification of oil adsorbed on palm decanter cake into methyl ester using sulfonated rice husk ash as heterogeneous acid catalyst - Noor, Hindryawati; Erwin, Erwin; Maniam, Gaanty Pragas (American Institute of Physics Inc., 2017)
Palm Decanter cake (PDC) which is categorized as the waste from palm oil mill has been found to contain residual crude palm oil. The oil adsorbed on the PDC (PDC-oil) can be extracted and potentially used as feedstock for biodiesel production. Feedstock from waste like PDC-oil is burdened with high free fatty acids (FFAs) which make the feedstock difficult to be converted into biodiesel using basic catalyst. Therefore, in this study, a solid acid, RHA-SO3H catalyst was synthesized by sulfonating rice husk ash (RHA) with concentrated sulfuric acid. The RHA-SO3H prepared was characterized with TGA, FTIR, BET, XRD, FE-SEM, and Hammett indicators (methyl red, bromophenol blue, and crystal violet). PDC was found to have about 11.3 wt. % oil recovered after 1 hour extraction using ultrasound method. The presence of sulfonate group was observed in IR spectrum, and the surface area of RHA-SO3H was reduced to 37 m2.g−1 after impregnation of sulfonate group. The RHA-SO3H catalyst showed that it can work for both esterification of free fatty acid which is present in PDC-oil, and transesterification of triglycerides into methyl ester. The results showed highest methyl ester content of 70.2 wt.% at optimal conditions, which was 6 wt.% catalyst amount, methanol to oil molar ratio of 17:1 for 5 hours at 120 °C.